Production of Microbial Cellulose Films from Green Tea (Camellia Sinensis) Kombucha with Various Carbon Sources - Treviño Garza, Mayra Zulema; Guerrero Medina, Ana S.; González Sánchez, Ricardo; García Gómez, Celestino; Guzmán Velasco, Antonio; Báez González, Juan Gabriel; Márquez Reyes, Julia Mariana (Molecular Diversity Preservation International, 2020)
The aim of this study was to evaluate the production of microbial cellulose films (MCFs) in culture media based on green tea and different carbon sources, using two microbial consortia (COr and CFr). During the fermentation process, there was a reduction in the total soluble solids (TSS) content and pH, as well as an increase in the acidity in all treatments. Furthermore, fluctuations in the total sugar content and proteins during the fermentation process were associated with the consumption of carbon and nitrogen sources, as well as the production of MCFs. In the color analysis, a decrease in the L* value was observed while the rest of the parameters remained stable. Production of films was observed between days 6 and 9 of fermentation; the preferred substrate for COr was glucose (wet base yields = 603.61% and dry base yields = 22.37%), whereas for CFr was dextrose (wet base yields = 601.49% and dry base yields = 28.14%). Finally, the MCFs produced by COr and CFr showed a homogeneous, thick appearance, slight flexibility, and the characteristic brown color of the fermentation medium.